Dietary Patterns, nutritional status and agricultural work performance of small-scale farmers in North West Pakistan - Din, Zia Ud; Khan, Zara; Haq, Zahoor Ul; Iqbal, Mudassar; Iqbal, Zafar; Khan, Imran; Ahmed, Zahoor; Paracha, Parvez Iqbal (Progress in Nutrition, 2019)
Dietary patterns examined to assess the overall dietary intake in relation to various health outcomes that may influence physical work capacity of small scale farmers. This follow up study was limited to the farming community of District Mardan, North West Pakistan. Initially, a primary cohort of 1200 farmers was randomly selected using two-stage cluster sampling method; the whole cohort was screened for nutritional status including body weight, height, blood hemoglobin level (Hb) and blood pressure. A sub-cohort of 452 farmers was extracted randomly from the primary sample for follow up; these farmers were followed to gather detailed information on relevant parameters i.e. routine daily working hours in the farm, agricultural, socio-demographic and health characteristics, and dietary intake. Data on nutritional status of the sub-cohort was extracted from the project record; all data was analyzed accordingly using appropriate statistical tests such as Analysis of variance (ANOVA) and logistic regression analysis. Three major dietary patterns were identified: ‘energy rich’, ‘mixed’, and ‘red meat’. Energy rich pattern was found strongly associated with farmers’ body mass index (BMI) and moderately associated with systolic (SBP) and diastolic blood pressures (DBP). Red meat pattern was associated with the risk of high blood pressure among the farmers. Among the nutritional indicators, only Hb had strong correlation with ‘mixed dietary pattern’ score. Working hours in the farm (farmers’ physical work capacity) had significantly strong correlation with the ‘mixed dietary pattern’ score; this association was further confirmed in logistic regression after adjusting for potential confounding factors. Compared to farmers in lowest quartile of ‘mixed dietary pattern’, those in the highest quartile had higher work performance after adjusting for covariates (adjusted OR: 0.81, 95% CI: 0.2 – 1.9). Findings of the current research study explained the key role of dietary patterns in farmers’ nutritional status and working potential. These results are important, particularly considering the fact that agricultural practices in developing countries are mostly physically demanding, especially in small scale farming. Poor nutritional status adversely affects farmers’ health that results in decreasing physical working capacity.